Democracy and The Nature Of African States: Towards an Institutional Reform For African Development - Gabriel Asuquo (Jurnal Office, 2020)
Democracy is a political culture that seeks to promote majority participation in the process and art of governance, with the aim of developing a society; based on the principles of equality, freedom and social justice. This implies that democracy must operate within the confines of a State structure, which means there must be a State before we can talk about the enthronement of democratic culture and institutions. Thus, this paper examined the nature of African States and discovered that Africans are operating a dislocated state structure that is at far variant, with Universal Characteristics of a State. This is so because the contemporary African States are part of African colonial legacy and the failure of African peoples to evolve after 50 years of colonialism are responsible for this state of affairs. Hence, the paper defended the thesis that until Africans reform their institutional arrangement, to reflect the Universal Characteristics of a State Structure, democracy in Africa will not deepen, and development will keep eluding the continent and her people. This reform agenda which the paper is proposing is premised on traditional African values and spirituality. The paper employs the method of critical analysis.